Coaching for performance the principles and practice of coaching and leadership - Whitmore, John 1937-2017 (Nicholas Brealey Publishing, 2017)
"Coaching for Performance is the proven resource for all coaches and pioneers of the future of coaching." Magdalena N. Mook, CEO, International Coach Federation (ICF)The seminal book featuring the powerful GROW modelCoaching for Performance is the institution of the coaching profession. This landmark text has now undergone the largest revision yet in its history to bring it fully up to date for today's professionals. With a focus on coaching as a way of being rather than a temporary process, this new edition explains how coaching can have a profound effect on the culture of an organisation. No longer an activity conducted in isolation by a select few managers, coaching impacts the growth of the whole company as well as the personal growth of the individual. This new edition includes a Foreword by John McFarlane, Chairman of Barclays and TheCityUK. New chapters on culture change demonstrate how to build a high performance culture in any type of organisation and measure the results. Extensive illustrative material has been added; the visuals are those used in coaching training programmes by Performance Consultants International, one of the pioneering global firms in coaching, leadership development and performance improvement. Terminology has been revised throughout to align with that used by the International Coach Federation and a new full glossary of terms serves to make this the definitive book on the topic. The influential GROW model (Goals, Reality, Options, Will) featured in the book is supported by new international studies and examples which are included throughout, ensuring that this edition will stay at the forefront of professional coaching and leadership development.